MANIPULATOR CONTROL SYSTEM BASED ON HUMAN BIOELECTRIC SIGNALS - Andrey A. Boshlyakov; Maksim I. Zharkov; Nikita A. Shilov (Известия Томского политехнического университета: Промышленная кибернетика)
The article provides an overview of various methods of manipulator control, gives the reason of selecting a specific method based on the certain requirements for working conditions. The authors selected the hardware for the method implementation and considered the methods of filtering the master signal, as well as the ways of converting it into a manipulator control signal.